The one-stop-shop approach: Navigating lumbar 360-degree instrumentation in a single position - Schwendner, Maximilian; Liang, Raimunde; Butenschön, Vicki M.; Meyer, Bernhard; Ille, Sebastian; Krieg, Sandro M. (Frontiers in Surgery, 2023)
Objective: Treatment strategies of patients suffering from pyogenic spondylodiscitis are a controverse topic. Percutaneous dorsal instrumentation followed by surgical debridement and fusion of the infectious vertebral disc spaces is a common approach for surgical treatment. Technical advances enable spinal navigation for dorsal and lateral instrumentation. This report investigates combined navigated dorsal and lateral instrumentation in a single surgery and positioning for lumbar spondylodiscitis in a pilot series. Methods: Patients diagnosed with 1- or 2-level discitis were prospectively enrolled. To enable posterior navigated pedicle screw placement and lateral interbody fusion (LLIF) patients were positioned semi-prone in 45-degree fashion. For spinal referencing, a registration array was attached to the pelvic or spinal process. 3D scans were acquired intraoperatively for registration and implant control. Results: 27 patients suffering from 1- or 2-level spondylodiscitis with a median ASA of 3 (1-4) and a mean BMI of 27.9±4.9 kg/m2 were included. Mean duration of surgery was 146±49 min. Mean blood loss was 367±307 ml. A median of 4 (4-8) pedicle screws were placed for dorsal percutaneous instrumentation with an intraoperative revision rate of 4.0%. LLIF was performed on 31 levels with an intraoperative cage revision rate of 9.7%. Conclusions: Navigated lumbar dorsal and lateral instrumentation in a single operation and positioning is feasible and safe. It enables rapid 360-degree instrumentation in these critically ill patients and potentially reduces overall intraoperative radiation exposure for patient and staff. Compared to purely dorsal approaches it allows for optimal discectomy and fusion while overall incisions and wound size are minimized. Compared to prone LLIF procedures, semi-prone in 45-degree positioning allows for a steep learning curve due to minor changes of familiar anatomy.